Assessment of Ni accumulation capability by fungi for a possible approach to remove metals from soils and waters. Issue 3 (4th March 2017) - Cecchi, Grazia; Roccotiello, Enrica; Di Piazza, Simone; Riggi, Alex; Mariotti, Mauro Giorgio; Zotti, Mirca
ABSTRACT: Abandoned industrial sites and mines may constitute possible hazards for surrounding environment due to the presence of toxic compounds that may contaminate soils and waters. The possibility to remove metal contaminants, specifically nickel (Ni), by means of fungi was presented exploiting a set of fungal strains isolated from a Ligurian dismissed mine. The achieved results demonstrate the high Ni(II) tolerance, up to 500 mg Ni l −1, and removal capability of a Trichoderma harzianum strain. This latter hyperaccumulates up to 11, 000 mg Ni kg −1, suggesting its possible use in a bioremediation protocol able to provide a sustainable reclamation of broad contaminated areas.